Tourism, Mountain, and ‘Mystic Fire’: A Study on Spiritual Journey of a Vedic Sadhak Living in Panchasee Mountain in Central Nepal (Journal of Tourism and Himalayan Adventures, 2023)
This paper is on spiritual tourism associates: tourism, ecology, and spirituality in the specific context of Panchasee mountain in the central Nepal. It presents spiritual experiences of a Vedic sadhak, born and raised in the west, lived in Sri Aurobindo Ashram in India for forty years from his young age and now has been living in Panchasee. Its key concern is to understand his spiritual quest in the Himalayan ecology. Focused on the stage of the spiritual transformation of the sadhak’s inner journey it reveals that the sadhak is highly energized to remain close with his spiritual wisdom that he experienced in Panchasee ecology and being active as a member of a family of the mountain society. It concludes with some insights in relation to spiritual tourism. This study has adopted a special research strategy called fursad ethnography to generate data on the sadhak’s life history and his spiritual quest in the Panchasee mountain.